Biomarker Tumor pada Kanker Paru - Muhartono; Dimas (Medula, 2021)
Tumor markers play an important role in cancer detection and guide patient management. In healthy asymptomatic individuals, biological markers can be used to identify sufferers at high risk of developing malignancy and in screening for early cancer. After diagnosis of malignancy, biomarkers can be used in determining prognosis, prediction of advance therapy, postoperative surveillance and monitoring response to ongoing therapy. Biomarkers are simply defined as components that can be used to distinguish abnormal and normal images, making for better diagnostic measures for lung cancer that facilitate early detection of disease, therefore enabling effective interventions, are needed to reduce lung cancer mortality. in both men and women, lung cancer is the most frequently diagnosed cancer and the leading cause of cancer death. In addition, the incidence rate is increasing in many countries. Many lung cancer patients have a poor prognosis because it is usually diagnosed at an advanced stage. Therefore, there is an urgent need to develop effective methods for early diagnosis of lung cancer. Several systematic reviews have evaluated the value of biomarkers for diagnosing lung cancer. However, it is still unclear which biomarkers have superior performance for early and accurate detection of lung cancer. This literature review presents the potential of biomarker detection which in the future can be developed into major biomarkers that are more beneficial for patients.